2017
DOI: 10.3390/molecules22122277
|View full text |Cite
|
Sign up to set email alerts
|

PP2A as the Main Node of Therapeutic Strategies and Resistance Reversal in Triple-Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC), is defined as a type of tumor lacking the expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). The ER, PR and HER2 are usually the molecular therapeutic targets for breast cancers, but they are ineffective for TNBC because of their negative expressions, so chemotherapy is currently the main treatment strategy in TNBC. However, drug resistance remains a major impediment to TNBC chemotherapeutic treatment. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 155 publications
(190 reference statements)
0
7
0
Order By: Relevance
“…PP2A hyperphosphorylation, as well as upregulation of the endogenous PP2A inhibitors such as SET, has been reported as main molecular mechanisms of PP2A inhibition in many tumors including breast cancer. These alterations have progressively emerged as promising therapeutic targets in this disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Although it has been recently reported that PP2A inhibition is a frequent alteration in breast cancer related with poor outcome and therapy resistance, such studies have been carried out in cohorts including cases with different molecular subtypes [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PP2A hyperphosphorylation, as well as upregulation of the endogenous PP2A inhibitors such as SET, has been reported as main molecular mechanisms of PP2A inhibition in many tumors including breast cancer. These alterations have progressively emerged as promising therapeutic targets in this disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Although it has been recently reported that PP2A inhibition is a frequent alteration in breast cancer related with poor outcome and therapy resistance, such studies have been carried out in cohorts including cases with different molecular subtypes [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPP2R2B belongs to the phosphatase family, and they are involved in several biological processes. Previous reports have shown that PP2A can activate Tcell responses by inhibiting cytotoxic T-lymphocyte-associated (CTLA)-4 function or impairing programmed death-ligand (PD-L)-1 expression [25]. The PPP2R2B gene can encode the regulatory subunit B55β, forming the PP2A-B55β complex by binding to the scaffolding and catalytic subunits.…”
Section: Chromosome 5q32 and 11p12mentioning
confidence: 99%
“…Inhibition of PP2A has been associated with poor prognosis of breast cancer [62]. PP2A regulates the expression of estrogen receptor (ER), a key molecular determinant of breast cancer status and survival [62,63]. PP2A activation was raised as an effective treatment target in MCF-7 breast cancer cell line through its mediation of ERα expression via modulating ER mRNA stability [64].…”
Section: Molecular Docking Studiesmentioning
confidence: 99%